Fostering Arabic Speaking Proficiency Through Ahaslides-Based Instructional Materials: A Qualitative Study in Indonesian Secondary Education - Nur, Dafa; Zulheddi (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to explore the implementation of Ahaslides-based instructional materials in the teaching of Arabic speaking skills (maharah al-kalām) among seventh-grade students at MTs Ira Medan. Employing a qualitative approach with a naturalistic research design, the study seeks to understand the teaching process in a contextual and in-depth manner. Data were collected through observations, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that the integration of Ahaslides fosters an interactive and engaging learning environment that encourages students’ active participation in speaking Arabic. Digital features such as the spinner wheel, Q&A, and match pairs help build students’ confidence, enhance vocabulary acquisition, and reinforce their understanding of sentence structure. Supporting factors include sufficient school infrastructure, teacher creativity, and student enthusiasm. However, challenges such as limited access to devices and unstable internet connections were also identified. Overall, Ahaslides demonstrated potential effectiveness in promoting Arabic speaking skills and offers an innovative alternative for technology-integrated language instruction.